2021
DOI: 10.1098/rsos.202192
|View full text |Cite
|
Sign up to set email alerts
|

The economic potential of metalliferous sub-volcanic brines

Abstract: The transition to a low-carbon economy will increase demand for a wide range of metals, notably copper, which is used extensively in power generation and in electric vehicles. Increased demand will require new, sustainable approaches to copper exploration and extraction. Conventional copper mining entails energy-intensive extraction of relatively low-grade ore from large open pits or underground mines and subsequent ore refining. Most copper derives ultimately from hot, hydrous magmatic fluids. Ore formation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 158 publications
(266 reference statements)
1
28
1
Order By: Relevance
“…Based on our resistivity model, we propose a mechanism for the evolution of a supercritical geothermal reservoir (Figure 10). The dacitic and andesitic melt below the supercritical geothermal reservoir may supply magmatic fluids to the supercritical geothermal reservoir (Blundy et al., 2021; Heinrich, 2005; Sillitoe, 2010). Upwelling supercritical fluids supplied from the melt are found to become trapped under a less‐permeable silica sealing, and supercritical fluids accumulated below the silica sealing as a result (Figure 10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our resistivity model, we propose a mechanism for the evolution of a supercritical geothermal reservoir (Figure 10). The dacitic and andesitic melt below the supercritical geothermal reservoir may supply magmatic fluids to the supercritical geothermal reservoir (Blundy et al., 2021; Heinrich, 2005; Sillitoe, 2010). Upwelling supercritical fluids supplied from the melt are found to become trapped under a less‐permeable silica sealing, and supercritical fluids accumulated below the silica sealing as a result (Figure 10).…”
Section: Discussionmentioning
confidence: 99%
“…We consider magmatic supercritical fluids as NaCl‐H 2 O fluids because magmatic fluids mainly consist of water and chloride salts (Blundy et al., 2021; Heinrich, 2005; Monecke et al., 2018; Richards, 2011; Sillitoe, 2010). The electrical resistivity of NaCl‐H 2 O fluids has been studied extensively in the relationship between subsurface resistivity models and geological structures (Bannard, 1975; Nono et al., 2020; Quist & Marshall, 1968; Sakuma & Ichiki, 2016; Sinmyo & Keppler, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, the fluid inclusions in these salt crystals are characterized by different high temperatures. The majority of nonferrous metals derive ultimately from igneous processes associated with magmatism (Blundy et al, 2021). This conclusion suggested that geothermal fluids provided both a circumstance of high temperature and Ca-rich brine for polyhalite formation.…”
Section: Formation Condition and Ore-formed Fluid Evolution Of Polyhalite Depositsmentioning
confidence: 96%
“…Numerical simulations with models that can handle high‐temperature multiphase flow of NaCl‐H 2 O fluids in porous media can help quantify the dynamic behavior of mass and heat transfer in magma‐related hydrothermal systems (Ingebritsen et al., 2010). Previous studies focused on the physical hydrology of porphyry and epithermal deposits (Blundy et al., 2021; Weis et al., 2012) and active hydrothermal systems (Andersen et al., 2015; Coumou et al., 2008; Gruen et al., 2014; Hasenclever et al., 2014; Kissling et al., 2015). In these models, permeability values are typically used as bulk parameters, and where high‐permeability fault zones have been considered, they are resolved by fine mesh sizes, which is computationally expensive.…”
Section: Introductionmentioning
confidence: 99%